2020
DOI: 10.17951/pjss.2020.53.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Ferrum concretions forms in the mollic gley soils of Low (Male) Polissya

Abstract: <p>In the humid conditions, the most common ground forms are the ferruginous ones: ferrum concretions, marsh ore, ocher spots, etc. Mollic gley soils are widely spread along the periphery of marshes and are formed under the influence of mollic and gley processes on various soil-forming rocks under conditions of sporadically pulsating water regime and excessive moisture under the meadow and swamp biocenoses. The ferrum concretions are characteristic of all genetic horizons of mollic gley soils, except for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the laboratory Fe-Mn washing of specific neoplasms on sieves and determination of their content and fractional composition by thermostatic-weight method has been carried out (Pankiv, 2019). Our research found that the gross content of Fe2O3 in the studied soils and especially in Fe-Mn specific tumors is significant, which indicates the important role of iron in the diagnosis of genesis and soil-forming processes (Pankiv et al, 2020a). However, information about the forms of Ferrum in the studied soils and soil concrete neoplasms is missing, which complicates the establishment of their genesis and intensity, the direction of soil-forming processes.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…In the laboratory Fe-Mn washing of specific neoplasms on sieves and determination of their content and fractional composition by thermostatic-weight method has been carried out (Pankiv, 2019). Our research found that the gross content of Fe2O3 in the studied soils and especially in Fe-Mn specific tumors is significant, which indicates the important role of iron in the diagnosis of genesis and soil-forming processes (Pankiv et al, 2020a). However, information about the forms of Ferrum in the studied soils and soil concrete neoplasms is missing, which complicates the establishment of their genesis and intensity, the direction of soil-forming processes.…”
Section: Methodsmentioning
confidence: 67%
“…Profile-differentiated soils formed on loamy and clay rocks of different genesis are the most complexly organized and informationintensive, which causes genetic and classification problems. Based on morphological analysis, it has been found that the studied soils are characterized by a similar set of genetic horizons and eluvialilluvial type of profile, but are formed with the participation of different direction and intensity of soil-forming processes (podzolization, lessivage, glee-eluvization, intrinsic alumina) (Pankiv et al, 2019b;2020c). The results of gross chemical analysis of soil, silty fraction, soil neoplasm are the most informative for diagnosing the intensity and direction of soil-forming processes.…”
Section: Methodsmentioning
confidence: 99%
“…Profile textural-differentiated soils (non-classification concept that combines different soils with vertical differentiation of granulometric and gross chemical composition of fine soil in the soil profile) of humid regions of the world (Luvisols, Retisols, Planosols, Acrisols, etc.) are formed on loamy and clay substrates of different genesis, they are one of the most organised and informational capacities (Bronnikova et al 2005, Quénard et al 2012, Smaga 2016, Pankiv et al 2020. Two types of profile textural-differentiated soils -sod-podzolic (Stagnic Retisols) and brown-podzolic (Neocambic Gleyic Retisols) ones (WRB 2014) -which have a similar set of genetic horizons, are distinguished on the basis of a soil research in the Cis-Carpathian region within Ukraine, but their profiles are formed with the participation of different elementary soil-forming processes, their orientation and intensity.…”
Section: Introductionmentioning
confidence: 99%